The effectiveness of detention pond in urban area - Amalia Husna, Mohamad Salim (2018)
Rapid urbanization has cause changes to the environment especially the topography of the land. By clearing the land and forests, the rate of infiltration into the ground will reduce. It will create a large quantity of stormwater runoff that will lead to flooding. In Urban Stormwater Management Manual for Malaysia Second Edition (MSMA 2), detention pond is applied to solve the problem regarding urban stormwater. The main objective of this study is to construct hydrograph and estimate the peak discharge for conceptual model of dry and wet detention pond. Rainfall-runoff relationship experiment is conducted for three stormwater cases; upstream, whole catchment and multiple storm whole catchments. This experiment is carried out by using Hydrology Apparatus in Hydraulic & Hydrology Laboratory, Universiti Malaysia Pahang. Conceptual model of dry and wet detention ponds were placed at the middle and end of Hydrology Apparatus. Detention can be divided into two types, dry and wet detention pond. For this case, large (50 cm x 24 cm x 10 cm) and small (32 cm x 24 cm x 10 cm) sizes of pond were used. Detention ponds are built to collect stormwater runoff temporarily and release them slowly to waterway. Peak flow and runoff volume after development must be higher than before development. Therefore, detention pond needs to be built for peak flow and volume of runoff reduction. In this experiment, large dry pond and large wet pond located at the end of Hydrology Apparatus has the smallest value of peak flow, longest time to peak and has the lowest runoff volume. This experiment proves that the two types of detention pond are effective for urban area.